Latent Autoimmune Diabetes of the Adult (LADA) in a Brazilian Indian - Vieira Filho, João Paulo Botelho; Moisés, Regina Célia Santiago; Sá, João Roberto de; Chacra, Antonio Roberto; Dib, Sergio Atala (São Paulo Medical Journal, 2001)
CONTEXT: Latent autoimmune diabetes of the adult (LADA) as originally described represents perhaps as many as 10 – 20% of adult-onset patients with diabetes. DESIGN: case report. CASE REPORT: A 38-year-old Brazilian Xavante-Jê Indian with Latent Autoimmune Diabetes of the Adult (LADA) is described, coming from the Sangradouro community in Poxoréu, Mato Grosso. The onset of diabetes after reaching 25 years of age, the evolution to insulin deficiency after a period of insulin-independence and the presence of auto-antibodies to glutamic acid decarboxylase (GAD) characteristic of LADA were present. This patient may represent the first case of LADA in a Brazilian with full Indian heritage. Further studies are necessary to verify the prevalence of this new type of diabetes in this population that does not have Caucasoid admixture and has a particular environmental background.